(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
The idea of health policy at the time with the adoption of the Amsterdam Treaty (1997) was to achieve a new direction, ie to approach diseases, reduce the likelihood and prevent the future emergence of a danger to human health. However, with the advent of the global challenge called COVID-19, there was a need to put the health back on the pedestal as the most important, less neglected, aspect that institutions need to focus on, because there is no doubt that we are in a situation in which even world leaders have left room to express uncertainty about how to respond to the emerging, hitherto unknown situation for all of us, not knowing what lies ahead and what steps need to be taken to strengthen health capacities on national, regional and international level. Health as a moving segment in the world that should be constantly taken into account, as well as the opening of the question of what health policies are pursued by the institutions of the European Union regarding health issues will be elaborated in detail in this scientific paper.